Penerapan Pembelajaran Blended Learning Dengan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Kemampuan Menganalisis Pada Mata Pelajaran Ekonomi Siswa Kelas XI Ips SMA N 1 Andong - Muflikasari, Rima; , Agus Susilo, S.Pd., M.Pd (2017)
The research goal is to knowing difference the ability for analyse on the subjects economy students of class XI IPS Senior High School 1 Andong between the use of blended learning with problem based learning models and problem based learning models without blended learning. The problem of this research is the ability to analyze student is low in the subjects economy. While the hypothesis in this research is there are differences in the ability to analyse on the subjects economy with difference learning model. The is an action class research with experimental design. The population of this research are students in grade XI IPS Senior High School 1 Andong. From this population as a sample taken two classes, namely class XI IPS 1 34 student as the experimental class and XI IPS 2 33 student as the control class. In experiments class applied Blended Learningwith Problem Based Learningmodelswhilein experiments class apllied Problem Based Learning models.Methods of data collection in this study are the documentation, test and questionnaire. The result show the average pre test class of experiments = 61,97 and average = 61,00 of the control class.While average pre test class of experiments = 75,38 and average = 68,73 of the control class. Based on normality testcan be concluded that the two groups is normal with a signification level of> 5% (0,05). While result from homogenity test show that the two groups spring from same population with a signification level of > 0,05. And then result from t-Test stated that Ho rejected and Ha accepted because thitung > ttabel (1,699). Based on this research, the was different betwen learning achievement the experimental class (blended learning with problem based learning models) and than class control (problem based learning models).